Implementation Of Naïve Bayes Algorithm For Children's Clothing Recommendation - Sutaryana, Yudi; Kharisma, Lalu Puji Indra (Jurnal Info Sains : Informatika dan Sains, 2024)
Many buying and selling activities are carried out online, which is very easy for buyers. One of themn the purchases of children's clothing, when buying clothes children for in choosing a garment, is sometimes very confusing there are many interesting choices. Apart from this, several factors are taken into account such as body type, material, color and price. From these factors, a system of recommendations necessary when purchasing children's clothing, in those online. The Naïve Bayes algorithm is a simple probabilistic classification which a set of probabilities by adding the frequencies. Naïve Bayes is supposed to provide accurate determining recommendations regarding clothing for women such as style, price, rating, size, neckline, length of sleeve, size, material, fabric type, decoration, pattern type, recommendation.